Contribution of the Peruvian Society of Obstetrics and Gynecology to the development of sexual and reproductive health and sexual and reproductive rights in Peru - Távara Orozco, Luis (2017)
Objective: To determine the number of articles and topics related to sexual and reproductive health and sexual and reproductive rights that have been published by Peruvian Society of Obstetrics and Gynecology in The Peruvian Journal of Gynecology and Obstetrics and other publications in the period 1993-2016. Methods: We reviewed the Journal database and identified issues related to sexual and reproductive health and sexual and reproductive rights published during 1993-2016, the term of the current Editorial Board. Related titles were grouped in order to facilitate their classification and appear consecutively according to date of publication. In addition, other publications of the Peruvian Society of Obstetrics and Gynecology during the same period were revised. Results: A total of 130 articles on sexual and reproductive health and sexual and reproductive rights were published in The Peruvian Journal of Gynecology and Obstetrics representing 14.18% of the total number of articles in this period. The highest proportion of papers was related to maternal mortality and family planning. In addition we found 74 papers published in other documents and 3 books. Conclusion: The highest proportion of papers on sexual and reproductive health was related to maternal mortality and family planning.